To solve the equation \( -2 - 8x = 4x - 2 \), we can follow these steps:
-
Move all terms involving \( x \) to one side of the equation and constant terms to the other side.
We will add \( 8x \) to both sides of the equation to isolate the \( x \) terms on one side:
\[ -2 - 8x + 8x = 4x - 2 + 8x \] This simplifies to: \[ -2 = 12x - 2 \]
-
Now, add 2 to both sides to isolate the \( x \) term:
\[ -2 + 2 = 12x - 2 + 2 \] This simplifies to: \[ 0 = 12x \]
-
Now, divide both sides by 12 to solve for \( x \):
\[ x = \frac{0}{12} = 0 \]
Thus, the solution to the equation \( -2 - 8x = 4x - 2 \) is:
\[ \boxed{0} \]